Water Temperature’s Effects towards Setting Time of Normal Type Alginate Impression Material - Pratiwi, Deviyanti; Sutrisno, Juanita Andriani (Indonesian Dental Association, 2020)
Introduction: Alginate impression material is widely used in dentistry. There are two types of alginate impression based on the setting time: fast setting (type I) and normal setting (type II). Setting time of alginate impression is affected by the ratio of powder and water, water temperature, also types of the alginate impression. In some dental treatments, dentists need to make modifications of alginate impression materials in the normal setting type to speed up the setting time and prevent maintenance delays. Objective: The objective of this study is to determine the effect of water temperature on the setting time of normal type alginate impression material. Methods: This laboratory experimental study were carried out on alginate impression materials of normal type which were tested in three temperature groups (±15°C, ±24°C, and ±40°C). The setting time is measured using a penetrometer in accordance with ANSI/ADA No. 18 equipped with a glass plate and a metal ring mold with a diameter of 30 mm and a height of 16 mm. Results: The results of statistical tests indicate the influence of water temperature on the setting time of the normal type of impression material carried out in all three temperature groups (p<0.05). Mann Whitney Test Results with p<0.05 showed a difference in the average setting time of each temperature group, in which the three groups are ±24°C to ±15°C, ±24°C to ±40°C, and ±15°C to ±40°C. The fastest setting time occurs in the test group with a temperature of ±40°C and the longest occurring in the testing group is ±15°C. Conclusion: There is an increase in the setting time of alginate impression materials in the normal setting type due to the influence of water temperature. Increased setting time by 23,2% faster at the temperature of ±40°C than the normal water temperature.